"A Very Steep Climb": Therapists' Perspectives on Barriers to Disclosure of Child Sexual Abuse Experiences for Men. Issue 6 (18th August 2017) - Gruenfeld, Elizabeth; Willis, Danny G.; Easton, Scott D.
ABSTRACT: Recent studies indicate that men experience unique barriers to disclosure of child sexual abuse. Blind spots held by mental health providers and social service agencies may inadvertently help produce and sustain these barriers. However, therapists who specialize in treating this population may also hold important insights into the barriers clients face. Because delayed and nondisclosure of child sexual abuse have been associated with negative mental health outcomes for adult survivors, understanding these barriers is critical to improve clinical practice and facilitate help-seeking. Using conventional content analysis, this study examined the perceptions of nine therapists who specialize in the treatment of men who were sexually abused in childhood, many of whom are considered pioneers in the field. Analyses identified nine types of barriers, which were organized into three categories: intrapersonal experience (difficult feelings, lack of language, and self-engagement), social milieu (internalized social stigma, negative responses, social loss or judgment, and masculine identity dissonance), and health care environment (structural barriers, relational challenges with therapists, and unhelpful therapeutic strategies). Implications for future research, clinical training, and clinical practice are discussed.